Use motion games in exercise with children with bronchial asthma - Полковник-Маркова, Вікторія Сергіївна; Дугіна, Ліана Вячеславівна (Slobozhanskyi Herald of Science and Sport, 2016)
Polkovnyk-Markova V., Dugina L. Purpose: to analyze the possibility of using moving games in the rehabilitation of children with bronchial asthma. Material & Methods: the modern scientific literature on integrated prevention and treatment of children with asthma. Results: A high frequency of morphological and functional deviations at children with asthma. Classification and examples of mobile games, which can be used for this group of children. Conclusions: the results of modern research that show the effectiveness the use of physical rehabilitation, including moving games.